Hubungan Motivasi kerja dan tingkat Pendidikan dengan Kinerja karyawan Balai Penelitian Bioteknologi Perkebunan Indonesia di Bogor - Ramlan Ruvendi; Abdulah . (Jurnal Ilmiah Binaniaga, 2007)
The fast changes in the work world at present demands adoption and adaptation abilities for the new skill and capabilities of human resources at every level. The coming changes needs a strategy to improve the existing one and in anticipating the future needs. In relation to human resource improvement target, the role of particularly human resource manager, is very important. Through this role, the employee’s performance can be directed effectively and efficiently especially towards the company’s goal.  An organization will reach a certain level of performance if the organization can create work condition that motivate individuals in the organization, growing good condition of collaboration between individuals and groups as well as creating creativity and initiative.  The performance of employees at BPBPI based on the evaluation on employees’ level of education conducted by DP2K in 2008 were 73.82 (Good) for Elementary, 75.82 (Good) for Senior High School, 78.20 (Good) for Non degree and 79.57 (Good) for Strata One (S1) Degree.  The connection between level of education and employee’s performance at BPBPI shows a strong and positive relation based on coefficient correlation test result where the value of r was 0.708.  An organization will reach a certain performance if it can create good condition of cooperation between individuals and groups and allow creativity and initiative to grow.